2014
DOI: 10.1111/jdv.12877
|View full text |Cite
|
Sign up to set email alerts
|

Dermatopathology in sub‐Saharan Africa: a systematic 5‐year analysis of all histopathological diagnoses from the Regional Dermatology Training Centre (RDTC) in Moshi, Tanzania

Abstract: In this African study inflammatory conditions are the main burden of skin diseases leading to a diagnostic biopsy. Our findings provide further evidence that KS, primarily related to the high prevalence of HIV infection is an epidemiological problem. Both SCC and basal cell carcinoma represent another relatively common malignant cutaneous neoplasms, reflecting the presence of specific populations at risk. The challenging spectrum of histological diagnoses observed in this specific African setting with basic wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…The majority of the histopathologic diagnoses were inflammatory conditions (51%), followed by tumors (38.3%) and infectious conditions (7.8%) (Tables and ). Similar data were published in other dermatopathological studies from Sub‐Saharan Africa . Clinical studies from Sub‐Saharan Africa reported higher skin infections (50–85%) suggesting that infectious skin diseases were not often biopsied.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the histopathologic diagnoses were inflammatory conditions (51%), followed by tumors (38.3%) and infectious conditions (7.8%) (Tables and ). Similar data were published in other dermatopathological studies from Sub‐Saharan Africa . Clinical studies from Sub‐Saharan Africa reported higher skin infections (50–85%) suggesting that infectious skin diseases were not often biopsied.…”
Section: Discussionsupporting
confidence: 87%
“…Another study found that in 78% of cases, the correct diagnosis was already included in the clinician's pathology requisition form [44]. A 5-year study in Tanzania looked at the case distribution and found a similar diagnostic spectrum, with the exception of the relatively high number of Kaposi's sarcoma and leprosy cases [45]. In addition to these two diseases, a similar study in Ethiopia reported high rates of cutaneous tuberculosis and leishmaniasis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Afirma, ademais, que no ocidente essa relação é inversa. Em outro estudo retrospectivo, apesar de proporção menor, mostrou maior incidência de CBC (11,12). O melanoma é o tipo menos frequente de câncer de pele e costuma ter prognóstico mais grave.…”
Section: Discussionunclassified